The grand prix companion - Henry, Alan, ....- (Cambridge : Icon books, 2007)
200,000 people attend the race weekend of each and every Grand Prix, and 300 million people watch every race live on TV - an annual global audience of 60 billion. This publication coincides with the build-up to the 2007 Formula 1 season. Author Alan Henry is the motor racing correspondent for the "Guardian", and edits "Autocar", "F1 Racing" and "Autocourse" (the Wisden of Grand Prix racing). Having covered over 520 Grand Prix races since 1973, and author of more than 40 books on Formula 1, Alan Henry now brings his unparalleled knowledge of the sport to a compendium of essential facts, statistics and exclusive anecdotes. It includes: F1's biggest secret, the Concorde Agreement; The most unusual rules, and how they are interpreted; Why safety is sexy; How many components make up a GP Car; How World Championship scoring evolved and changed; Why women can't drive; Who is the greatest?